Влијанието на финансиските институции врз макроекономската и финансиската стабилност - Николовска Вратеовска, Данче (Економски факултет, УКИМ, Скопје, 2014)
Financial system as a subsystem of the global economic system and social system in general, has an essential role in the efficient functioning of the global economy. Within each financial system, financial institutions are an integral part through which the national economy, directly and / or indirectly realizes its goals and objectives. Financial institutions are profit financial organizations, which develop methods, procedures and financial instruments that allow the collection of liquid financial assets from surplus economic units (savers) and channel them to the deficit economic units (businesses, population, etc.), from where they become financial intermediaries and major providers of efficient system for saving and investment in the economy. Since the foundation of the motive for their operation is profit, they place the funds or allocate the most successful and least risky projects, from which they actually participate in the efficient allocation of economic resources as the basic paradigm of the economic science. Whether in an economy dominated by banking and non-banking financial institutions, stability and development of the financial system, and thus stability and development of financial institutions as its main infrastructural mechanisms are essential for growth and economic development in that state. The stability and growth and development of the financial system is profoundly influenced by a range of factors: the quality, scope, level and effectiveness of regulation, supply and extent of the diversity of financial products and services, types and behavior of investors, transparency and accuracy of information, performance and preferences of the business sector, knowledge and culture of trading on the capital market, the continuity of the market, traditional values and cultural, social dimensions and aspects of the population, etc. Financial stability through the financial system and financial institutions are reflected in macroeconomic stability in general, through the support of quality investment decisions, efficient allocation of capital, and greater commitment to economic resources, lower unemployment and greater economic growth. Subject of research of this paper are: the importance of properly functioning financial system and the types of financial institutions (such as infrastructure elements of the financial system), determination of their functions, objectives and effects and thus their impact on the provision and maintenance of macroeconomic and financial stability, the nature and policies of macroeconomic stability and its interdependent linkage to financial stability and the role of financial institutions in the creation and spillover of economic crises (with special emphasis on the global economic crisis in 2008). Finally, the emphasis of research will be put on the situation in R. of Macedonia the structure, stability and performance of the domestic financial system and its implications on the domestic macroeconomic picture, consequences of the crisis, the strengths and weaknesses, and future needs and opportunities of the country, aimed at providing a higher degree of upgrowth of the financial system and economic growth and development in terms of a stable environment.
The impact of financial institutions on macroeconomic and financial stability
Докторска дисертација одбранета во 2014 година на Економскиот факултет во Скопје, под менторство на проф. д–р Владимир Филиповски.
Keywords: financial system, financial institutions, savings, investment, efficient allocation of resources, surplus economic units, deficient economic units, financial instruments, financial intermediaries, financial regulation, banking financial institutions, non-banking financial institutions, financial stability, financial services, economic growth, macroeconomic stability, macroeconomic policies